A Place to Speak and Be Heard: Building a Collection to Support the Use of Indigenous Languages in Canada's Parliament. Issue 2 (3rd April 2023) - Schneider, Ze'ev; Norman, Karen
Abstract: The authors describe a collection assessment project that focused on Indigenous language learning and reference material. The project, completed at the Library of Parliament, was motivated by Parliamentary committee reports addressing the use of Indigenous languages in Canada's Senate and House of Commons. The authors created an original bibliography representing all Indigenous language families in Canada and compared it to the library's holdings, which were also analyzed separately. Project outputs included a rejuvenated collection of Indigenous language reference and learning material; and a subject guide used to promote newly-acquired holdings and to facilitate access to online resources.